Gender Transformative Methodologies CoP. Reimagining intersectionality: Institutionalization of a concept, its complexity, illusions and contradictions - Feldman, Shelley; Farnworth, Cathy Rozel; Bailey, Arwen (2024)
For many gender specialists, intersectional research represents one of the most important theoretical contributions of gender and feminist analyses. This is because such research acknowledges complexity and hierarchy, and division and difference among members of any identity category, including, but not limited, to women. Intersectional research also acknowledges and seeks to understand power as a relational phenomenon within social groups as well as between them. In practice, this means that thinking with an intersectional lens exposes how all identity categories including race, class, and gender, but also, sexuality, ability, nationality and ethnicity, and indigenous/migrant are not homogenous categories. Rather, categories marking difference refer to populations that entail relations of both oppression and domination, opportunities, and constraints. Significantly, as well, an intersectional approach not only presumes that identities are always multiple but, also, that they can only be understood as intertwined, intersecting, and reciprocal rather than as simply additive. By recognizing this complexity, an intersectionality lens asks researchers to be cognizant of within category variation, especially when generalizing across comparative cases.